Defining creativity in Kangri: Innovation of change in the Kashmir Valley - Asim Sikandar; Shakeel
This article explores an innovative solution to address a century-old design limitation in the traditional Kashmiri Kangri, a cherished winter essential in the region. The introduction of the "Spill-proof Kangri" design, based on the principles of gyroscopic effect and gimbal lock, has successfully mitigated the issue of spillage, making it safer and more user-friendly. The National Innovation Foundation - India (NIF) has filed a patent application to protect this intellectual property and has actively supported its diffusion. Research into technology standardization and feedback from trials in the Kashmir valley have been encouraging, emphasizing the enhanced safety standards and potential for cultural preservation. The Spill-proof Kangri design represents a significant case of incremental innovation, highlighting the need for holistic development and adaptability in the value chain. It also underscores the importance of bridging the gap between innovations from the informal sector and formal scientific research. Collaboration is encouraged to disseminate this innovation and benefit end-users while preserving cultural traditions.